Komunikasi Terapeutik Perawat dengan Kepatuhan Minum Obat Hipertensi - Lahay, Maryam K.; Monayo, Edwina R; Azis, Moh. Nisyar Sy. Abd. (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the relationship between nurses’ therapeutic communication and medication adherence among elderly patients with hypertension. A cross-sectional design was employed using an accidental sampling technique involving 47 elderly respondents. The results showed a significant relationship between nurses’ therapeutic communication and antihypertensive medication adherence among the elderly (p-value = 0.000). In conclusion, higher levels of nurses’ therapeutic communication are associated with greater medication adherence among elderly patients.   Keywords: Therapeutic Communication of Nurses, Medication Adherence, Elderly